1977
DOI: 10.1056/nejm197712082972303
|View full text |Cite
|
Sign up to set email alerts
|

Hematologic Neoplasia in Patients Treated for Hodgkin's Disease

Abstract: We studied 680 patients with Hodgkin's disease, treated at Stanford University Medical Center from July 1, 1968, through December 31, 1975, to determine the risk of development of hematologic neoplasia. Six cases of leukemia occurred in patients in clinical remission, one 7 1/2 years after diagnosis. Two additional cases occurred in patients with active Hodgkin's disease. No cases were seen in 320 patients treated with radiotherapy alone or in 30 treated with chemotherapy alone. A single case of subacute leuke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
2
2

Year Published

1979
1979
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 422 publications
(69 citation statements)
references
References 23 publications
1
64
2
2
Order By: Relevance
“…[1][2][3] Our understanding of this serious late effect has evolved over time. Many early studies reported an increased risk of acute leukemia, which has a shorter latency and is associated with the use of alkylating chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Our understanding of this serious late effect has evolved over time. Many early studies reported an increased risk of acute leukemia, which has a shorter latency and is associated with the use of alkylating chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Results were apparently good, but unfortunately, a significant incidence of leukemia and sarcoma developed in these patients and the treatment was essentially abandoned (23). However, none of 320 patients with Hodgkin's disease treated with TLI has shown a hematologic neoplasm in a 10-year followup (24). Reasons for the marked difference in the tumorigenicity of the two radiation regimens is unclear but may be related to differences in fractionation, dose per fraction, ports, and megavoltage versus kilovoltage xrays.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, accurate delineation of the involved areas makes it possible to tailor treatment to the specific needs of the patient who may be spared the hazards of overtreatment and vulnerabilty to growth retardation, endocrine dysfunctions, and emergence of second malignancies. [27][28][29][30] Precise surgical staging, the advocates say, makes restaging for the assessment of therapy easier and patients who need more therapy can be identified earlier and treated properly. 31 Surgical staging has contributed to a great deal of understanding about the patterns of disease spread.…”
Section: Discussionmentioning
confidence: 99%